2015
DOI: 10.1016/j.annepidem.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of cancer attributable to occupational exposures

Abstract: Purpose To review the literature on the estimation of the population attributable fraction (PAF) of cancer due to occupational exposures and to describe challenges in the estimation of this metric. To help illustrate the inherent challenges, we also estimate PAFs for selected cancers diagnosed in the United States in 2010 attributable to work as a painter (causally associated with bladder and lung cancer) and shiftwork (possibly associated with breast cancer). Methods We reviewed and summarized previous repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 32 publications
1
55
1
6
Order By: Relevance
“…In a recent review, 7.1% of all bladder cancers in men (1.9% in women) in the UK were attributed to occupational exposure to carcinogens [48]. However, the global impact of occupational exposures on bladder cancer incidence remains difficult to assess and is likely to be relatively limited [49].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent review, 7.1% of all bladder cancers in men (1.9% in women) in the UK were attributed to occupational exposure to carcinogens [48]. However, the global impact of occupational exposures on bladder cancer incidence remains difficult to assess and is likely to be relatively limited [49].…”
Section: Discussionmentioning
confidence: 97%
“…However, a number of studies have found no association between cancer and shift work [64,65,66,67]. The variability in these findings may be related to other contributing factors, such as individual differences in susceptibility to carcinogenesis, occupational exposure to carcinogenic agents, and lifestyle [68,69]. Taken together, the literature suggests that further studies are needed to quantify and understand the relationship between shift work and risk of cancer.…”
Section: Cancermentioning
confidence: 99%
“…Of these occupational cancers reported, men were the most affected, as they were in our results, too. Although the consequences of this group of pathologies are very serious, research into occupational cancer is still rare (Gonzalez Sanchez, ; Purdue, Hutchings, Rushton, & Silverman, ) despite the data provided by the International Agency for Research on Cancer (IARC), which recognizes that there are around 150 physical or chemical agents which could possibly be carcinogenic present in workplaces (Lißner, Kuhl, Kauppinen, & Uuksulainen, ; Mattei et al, ). In our study, the prevalence rate of neoplasms was the lowest among all the illnesses studied, and these may not even be related to work.…”
Section: Discussionmentioning
confidence: 99%